Current Developments on the Role of α1-Adrenergic Receptors in Cognition, Cardioprotection, and Metabolism - Perez, Dianne M. (Frontiers in Cell and Developmental Biology, 2021)
The 1-adrenergic receptors (ARs) are G-protein coupled receptors that bind the endogenous catecholamines, norepinephrine and epinephrine. They play a key role in the regulation of the sympathetic nervous system along with  and 2-AR family members. While all of the adrenergic receptors bind with similar affinity to the catecholamines, they can regulate different physiologies and pathophysiologies in the body because they couple to different G-proteins and signal transduction pathways, commonly in opposition to one another. While 1-AR subtypes (1A, 1B, 1C) have long been known to be primary regulators of vascular smooth muscle contraction, blood pressure, and cardiac hypertrophy, its role in neurotransmission, improving cognition, protecting the heart during ischemia and failure, and regulating whole body and organ metabolism are not well known and are more recent developments. These advancements have been made possible through the development of transgenic and knockout mouse models and more selective ligands to advance their research. Here, we will review the recent literature to provide new insights into these physiological functions and possible use as a therapeutic target.